2005
DOI: 10.1159/000084644
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Related Variation in Song-Control Regions in Cassin’s Finches, <i>Carpodacus cassinii</i>

Abstract: Male Cassin’s finches (Carpodacus cassinii) sing long, complex songs that incorporate many elements mimicked from other species. Although one-year-old males (males in their first breeding season) are sexually competent and do breed, they sing a simpler song (fewer syllable types) than do males two or more years old (called after-second-year males). Females do occasionally sing, but with much less stereotypy and complexity than breeding males of any age. We collected brains from free-living breeding after-secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Similar age-related differences as those found in juncos were observed in another songbird, the Cassin's Finch (Carpodacus cassinii) [MacDougall-Shackleton et al, 2005], which also exhibits SY vs. ASY plumage differences, crystallizes song shortly before the first breeding season, and is thought to be capable of changing song repertoire yearly [Samson, 1978]. In Cassin's Finches, as in juncos, the volumes of HVC and RA did not differ in SY and ASY males, but Area X was smaller in the older birds (MAN was not measured).…”
Section: Resultssupporting
confidence: 77%
“…Similar age-related differences as those found in juncos were observed in another songbird, the Cassin's Finch (Carpodacus cassinii) [MacDougall-Shackleton et al, 2005], which also exhibits SY vs. ASY plumage differences, crystallizes song shortly before the first breeding season, and is thought to be capable of changing song repertoire yearly [Samson, 1978]. In Cassin's Finches, as in juncos, the volumes of HVC and RA did not differ in SY and ASY males, but Area X was smaller in the older birds (MAN was not measured).…”
Section: Resultssupporting
confidence: 77%
“…Collectively, these results suggest that there is a relationship between the complexity of a learned task and the amount of brain space devoted to that task. Somewhat surprisingly, there is a negative relationship between song complexity and Area X volume in the zebra finch (Airey and DeVoogd, 2000) and Cassin’s finch (Macdougall-Shackleton et al, 2005; also see Hamilton et al, 1998). While the significance of this finding us unclear, it underscores the value of examining multiple regions with potentially different functions within the vocal control system.…”
Section: Neuronal Attributes That Co-vary With Song Attributesmentioning
confidence: 98%
“…Traditional Nissl staining methods can define the borders of lMAN core, (Johnson and Bottjer, 1992). However, previous studies attempting to delineate volumetric variation in seasonally breeding birds have produced inconsistent results due to an inability to crisply delineate nucleus boundaries (Airey and DeVoogd, 2000; MacDougall-Shackleton et al, 1998; MacDougall-Shackleton et al, 2005). However, chemical neuroanatomical studies have revealed a variety of neuromodulatory proteins that do clearly delineate the boundaries of lMAN core and in some cases mMAN (Ball et al, 1988; Ball and Balthazart, 2010).…”
Section: Introductionmentioning
confidence: 99%